2005
DOI: 10.1152/jn.00359.2005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Strong Synaptic Coupling Between Single Tactile Afferents From the Sole of the Foot and Motoneurons Supplying Leg Muscles

Abstract: Evidence for strong synaptic coupling between single tactile afferents from the sole of the foot and motoneurons supplying leg muscles. J Neurophysiol 94: 3795-3804, 2005. First published August 3, 2005 doi:10.1152/jn.00359.2005. It has been known for some time that populations of cutaneous and muscle afferents can provide short-latency facilitation of motoneuron pools. Recently, it has been shown that the input from individual low-threshold mechanoreceptors in the glabrous skin of the hand can modulate ongoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 33 publications
(60 reference statements)
8
105
3
1
Order By: Relevance
“…2 -Analyses revealed that the number of units that fell within each classification did not differ from previous reports of receptors on the foot sole (P Ͼ 0.05; Fallon et al 2005;Kennedy and Inglis 2002). Similar to previous findings, there did not appear to be a clear pattern of receptor distribution across the foot sole (Kennedy and Inglis 2002).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…2 -Analyses revealed that the number of units that fell within each classification did not differ from previous reports of receptors on the foot sole (P Ͼ 0.05; Fallon et al 2005;Kennedy and Inglis 2002). Similar to previous findings, there did not appear to be a clear pattern of receptor distribution across the foot sole (Kennedy and Inglis 2002).…”
Section: Resultsmentioning
confidence: 61%
“…2 -Tests were used to determine differences in the number of receptors from each class between the present work and previous studies that have recorded from populations of skin afferents in the foot sole (Fallon et al 2005;Kennedy and Inglis 2002). Student's t-tests were used to determine the difference between the percentage of type I versus type II and the percentage of slowly adapting versus fast-adapting receptors that were reduced to 0% BFR.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…It is known that even brief noxious input can significantly interfere with the effects of training at the spinal level for long periods (Grau et al, 1998(Grau et al, , 2004Crown et al, 2002a,b;Ferguson et al, 2006). This putative effect of noxious cutaneous input is perhaps not surprising in light of the significant role that cutaneous input plays in locomotion (Bouyer and Rossignol, 2003;Fallon et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a short latency inhibitory pathway from plantar cutaneous afferents to ankle extensors following low-threshold stimulation to the posterior tibial nerve is enabled in spinal intact subjects when the foot sole contacts a surface (Abbruzzese et al, 1996). Excitation of cutaneous afferents arising from the sural nerve or foot sole induces long-lasting facilitation of the ipsilateral extensor motoneurons in the cat (Schieppati and Crenna, 1984) and human (Fallon et al, 2005) and induces crossed inhibitory postsynaptic potentials in the knee and ankle extensors (Edgley and Aggelopoulos, 2006). These effects may be related to the postulated action of plantar cutaneous afferents on the presynaptic inhibition acting on Ia afferent terminals (Iles, 1996), to their interaction with the machinery of reciprocal innervation (Rossi and Mazzocchio, 1988), and to their actions on Ib inhibitory pathways during which soleus exerts facilitation (instead of inhibition) to quadriceps when the triceps surae muscle is contracting (Pierrot-Deseilligny et al, 1981,1982.…”
Section: Introductionmentioning
confidence: 99%